2011
DOI: 10.1074/jbc.m111.218305
|View full text |Cite
|
Sign up to set email alerts
|

GINS and Sld3 Compete with One Another for Mcm2-7 and Cdc45 Binding

Abstract: Sld3 is essential for the initiation of DNA replication, but Sld3 does not travel with a replication fork. GINS binds to Cdc45 and Mcm2-7 to form the replication fork helicase in eukaryotes. We purified Sld3, Cdc45, GINS, and Mcm2-7 and studied their interaction and assembly into complexes. Sld3 binds tightly to Cdc45 in the presence or absence of cyclin-dependent kinase activity. Furthermore, Sld3 binds tightly to the Mcm2-7 complex, and a ternary complex forms among Cdc45, Mcm2-7, and Sld3, with a 1:1:1 stoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…We next found that Sld3 can form an interaction with Mcm2-7 with 1:1 stoichiometry in the absence of DNA and that GINS can form an interaction with Mcm2-7 with 1:1 stoichiometry in the absence of DNA (Fig. 8, D-F) (39). However, in the presence of ssARS1-2, the interaction between Sld3 and Mcm2-7 is disrupted (Fig.…”
Section: Replacement Of Origin Thymines With Adenines Completely Abolmentioning
confidence: 95%
See 3 more Smart Citations
“…We next found that Sld3 can form an interaction with Mcm2-7 with 1:1 stoichiometry in the absence of DNA and that GINS can form an interaction with Mcm2-7 with 1:1 stoichiometry in the absence of DNA (Fig. 8, D-F) (39). However, in the presence of ssARS1-2, the interaction between Sld3 and Mcm2-7 is disrupted (Fig.…”
Section: Replacement Of Origin Thymines With Adenines Completely Abolmentioning
confidence: 95%
“…When Sld3 is added to a GST-Mcm2-7 pulldown of GINS, Sld3 inhibits the interaction between GINS and Mcm2-7 (Fig. 7, C and D) (39). When ssARS1-2 is added to the GST-Mcm2-7 pulldown of radiolabeled GINS in the presence of competing Sld3, ssARS1-2 promotes the interaction between GINS and Mcm2-7 in a concentration-dependent manner (Fig.…”
Section: Replacement Of Origin Thymines With Adenines Completely Abolmentioning
confidence: 99%
See 2 more Smart Citations
“…Human TopBP1 was purified as described previously (49). Plasmids for E. coli recombinant expression of Dpb11 (wild-type and mutant) for GINS and for yeast in vivo expression of DPB11 (wild-type and mutants) were prepared as described previously (37,50). Yeast Dpb11 (wild-type and mutant), Mcm2-7, Cdc45, Sld3, Sld2, CDK, DDK, GINS, and GST were purified as described previously (37,46,48,51).…”
Section: Methodsmentioning
confidence: 99%